Proyecto de pre factibilidad para la creación de una empresa que se dedique a la elaboración artesanal de coladas hechas a base de zanahoria blanca y camote en el cantón Durán - Cano Cedeño, Johnny Ramón (2015)
This work is aimed at an analysis of pre-feasibility to create a company that is dedicated to the craftsmanship of castings (compote) made from sweet potato and white carrot directed and marketed in the Durán canton of Guayas province. In the project we intend to demonstrate that the sweet potato and white carrot crops grown in different regions of our country and which contain a high degree of nutritional value, consisting of vitamins and minerals needed for feeding children and the general public is the basis or the raw material of our feasibility study on the establishment of the company………..